A compact ultra‐wideband multiple‐input–multiple‐output antenna with dual band‐notched performance using slot‐line transmission. Issue 5 (29th January 2022) - Yuan, Hong; Zhang, Fu‐Shun; Zhang, Jun‐Jie; Feng, Yun‐Xia; Liu, Yuan‐Fei
Abstract: A compact ultra‐wideband (UWB) multiple‐input–multiple‐output (MIMO) slot antenna with dual band‐notched performance is presented. Unlike the traditional slot and Vivaldi antennas, the novel slot‐line to coplanar waveguide (S‐CPW) transmission structure improves the impedance of the antenna matching and realizes the wideband characteristics. By utilizing the odd mode operation of the S‐CPW structure, the in‐phase superposition radiation of four‐way open slots is realized. The isolation and the band‐notched characteristics are achieved by etching the T‐slot structure and loading the split‐ring resonators (SRRs), respectively. The actual design with the overall size of 0.25 × 0.25 × 0.006 λ0 3 (λ0 is the free space wavelength at the lowest operating frequency) has been fabricated and measured. The measured results demonstrate that the impedance bandwidth of the antenna is 2.5‑10.8 GHz for |S11| < −10 dB, and the notched band is 5.2–5.9 GHz and 6.6–7.3 GHz, respectively. Besides, the isolation of the proposed antenna is higher than 20 dB, and the antenna maintains relatively stable radiation characteristics and gain, as well as a lower envelope correlation coefficient (ECC < 0.004).